Peran Pengendalian Internal Dan Corporate Governance Dalam Pencegahan Fraud (Study pada perusahaan Konstruksi di Tangerang Selatan) - Pangaribuan, David (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2020)
Fraud behavior is loss action on many stakeholders whatever fraud behavior are extraordinary crime. This study aims to determine the effect of internal control and corporate governance on fraud prevention (empirical study of construction service companies in the south tangerang area). The population of this study are employees who work at construction service companies. The data were collected by using accidental sampling totaling 81 respondents. Hypothesis testing is done using a simple linear regression method. The results showed that partially internal control and corporate governance have an effect on fraud prevention. The mean that internal control and corporate governance have implication to prevention fraud on organization. That special have play to fitness organization performance.internal control one tools to prevention fraud on organization so that organization or company have must to climate culture and pushing employe commitment and working motivation